EKSPLORASI MUATAN NILAI KARAKTER DALAM KESENIAN ISLAM KENCRENG JAWA - Aziz, Rizky Maulana; Sidna, Nurilkaunaini (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2023)
This study aims to describe the content of character values in Javanese Kencreng Islamic Art and the function of values in the art, using a qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. Data validity was strengthened through source and technique triangulation. The results revealed that through the Javanese Kencreng art in Baitul Amin mosque, there are 14 character values embodied by members of the art group, including religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, love for the country, communicative, peace-loving, social care, and responsibility. The functions of these character values include the formation and development of individual potential, character improvement and strengthening, as well as the function of filtering positive values in society.